Alternative contracting for informal economy financing - Liles, Scott Day (School of Economics, 2023)
The informal economy in South Africa is a source of considerable debate. Academics and practitioners struggle to define, characterize, measure and place the informal economy in South Africa's macroeconomic picture. Despite the polemic, it is generally agreed that the informal economy is important. Every collection of ideas regarding the South African economy includes some thoughts on the informal economy. The compelling point is that these thoughts are generated in a wide variety of disciplines. The informal economy features in collections addressing economics, politics, history, urban planning and even literature. Christian Rogerson and Eleanor Preston-Whyte' s recent collection, "South Africa's Informal Economy", is testament to the broad application of the informal economy. Beyond the debate of definitions and characteristics is the debate on how to assist the informal economy. Leiman suggests that one of the major constraints on the informal economy is "blocked access”. Blocked access refers to limited access to product and factor markets. In the case of the informal economy this reference means limited access to raw materials, skills and capital. In South Africa the limited resources directed to informal economy activity can be largely attributed to past government policies that were hostile to the informal economy's existence and development. As such, the role of informal economy development was left to non-governmental and welfare organizations.